Optimization of airport ground fuel consumption with optimal speed profiles - Tan, Jasmine Wan Lin (2017)
Every industry has its own negative contribution to the environment and air transportation industry is one of the industries that are commonly thought of. The consistent strong increase in air travel demand over the decade has captured attention on airport ground fuel consumption and emissions. In early attempts, reduction in taxi fuel burn was targeted by reducing taxi time. Some have optimized taxi time and adopted stand-holding approach to reduce taxi fuel burn and emissions, while some proposed queuing models to reduce taxi time. In the recent years, studies on reducing taxi fuel burn and emissions produced various models that use detailed speed profiles to estimate taxi fuel burn, emissions and optimize taxi fuel burn. However, as airport ground congestion is still important, the optimization models included taxi time in the objective function as well. The recent studies adopted a multi-objective approach that optimize taxi fuel burn and taxi time simultaneously using optimal speed profiles, where a trade-off relationship between the two conflicting objectives is studied as well. As taxi time is always considered due to airport ground congestion, this report proposes an alternative linear optimization model that optimizes taxi fuel burn only, using optimal speed profiles and produces a conflict-free taxi process without runway queue, for all aircrafts. The model use least-fuel-burn routes and adopts stand-holding approach which transfer waiting times on taxiway with engines on due to conflicts and runway queues to gates with engines off. As such, delay is introduced to the given initial gate schedules to produce optimal gate schedules for aircrafts to taxi conflict-free and avoid runway queue. Ground congestion is not an issue since aircrafts taxi conflict-free and without runway queue. Model analysis is performed using Changi Airport Terminal 2 and sensitivity analysis study the impact of number of aircrafts, number of gates and proportion of heavy aircrafts on fuel burn and delay.